Self-knowledge and self-determination of the high school student in the perspective of the tutoring process. A theoretical-empirical analysis - Adrianna Sarnat-Ciastko; Wioletta Dziarnowska (Studia z Teorii Wychowania)
The article presents a theoretical-empirical analysis of the meaning and presence of self-knowledge and self-determination of high school students in the tutoring process. The theoretical foundations of self-knowledge and self-determination related to the philosophical and pedagogical personalist tradition are presented. The interrelation of these categories was verified in the research "What is school tutoring?" carried out on a group of 437 students from 18 high schools. As a result, it was shown that this form of work with a student is perceived positively by 78.5% of the study's participants and significantly activates the presence of their self-knowledge. This proves the vital importance of tutor accompaniment for building student well-being at school. It was concluded that the lower presence of self-determination as an effect of tutoring suggests the need to pay more attention to this aspect in the tutoring process.